Attitudes toward wildlife: The impact of physical attractiveness. Issue 12 (15th July 2020) - Harnish, Richard J.; Nataraajan, Rajan
Abstract: The current research examined whether perceived physical attractiveness of a species impacted participants' attitudes toward supporting and protecting the species. A sample of undergraduate students attending a public university located in the northeast United States were surveyed. Results indicated that across and within species the physically attractive animal received more support for protection than did the physically unattractive animal. Results are discussed in terms of perceptual and cognitive fluency.